Energy Expenditure in Infants in Health and Disease - Ross Shepherd (Canadian Journal of Gastroenterology)
Measurement of energy balance represents a basic theoretical concept in the determination of nutritional and fluid requirements in humans in health and disease. Infants have special nutrient requirements, more limited reserves and relative immaturity of organ function. Energy requirements of infants have been based either retrospectively on intakes required to achieve normal growth or on equations derived from energy expenditure studies performed early this century. Recently, improved techniques for studying resting energy expenditure (REE), total energy expenditure (TEE) and metabolically active body compartments in infants have facilitated more accurate estimates of energy requirements. Such studies indicated that current reference values for energy requirements are overestimates, and that compared with measured values, predicted values vary markedly between the various predictive equations with wide co-efficients of variation. In disease states with altered body composition, such as cystic fibrosis and end-stage liver disease, predictive equations markedly underestimate both energy and fluid requirements. In cystic fibrosis, both TEE and REE are 25% higher than values in healthy infants. In extrahepatic biliary atresia, energy expenditure per unit body cell mass is markedly elevated, suggesting that this is a catabolic condition in infants. Current estimates of energy and fluid requirements in both health and disease in infants need reappraisal. Bedside and free living energy expenditure methodology should be used to define accurately components of energy requirement in individual infants.